Survei Longitudinal Indonesia tentang Kesehatan Mental dan Faktor Sosial (INDOLUMEN): Hasil Awal dan Protokol - Edo Sebastian Jaya; Eko Hermanto; Shabrina Audinia; Shierlen Octavia; Salima Carter; Fadhilah Ramadhannisa (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
While many known risk factors and mechanisms for psychosis exist, the time it takes for these risk factors and mechanisms to influence psychosis remains unclear. Furthermore, the average duration of a psychotic symptom has not been estimated. The aim of the study is to discover the average duration of an episode of psychotic symptoms and other mental disorders, as well as the average duration by which psychological mechanisms of risk factors and psychotic symptoms or other mental disorders operate. This study is an online longitudinal survey with various time-interval assessments (baseline, 7 daily, 4 weekly, 4 fortnightly, and 6 monthly assessments). A community sample of Indonesians were recruited via internet and a sample of help-seekers were recruited from clinical practices. From November 2018 to March 2019, we recruited 464 participants who completed the baseline survey from the community. Of the 464 participants, 73% of them are female with ages ranging from 18 - 57 years and 33.2% reported having been diagnosed with at least one mental disorder. The expected results of the surveys provide us with estimates regarding appropriate time-intervals of risk factors and mechanisms of psychosis.